2001
DOI: 10.1038/sj.ijir.3900786
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster producing temporary erectile dysfunction

Abstract: Varicella Zoster affecting the sacral dermatomes is a rare but well recognised cause of urinary retention. Only one case of erectile dysfunction associated with Varicella Zoster has previously been described, which was longstanding, but no cases of transient erectile dysfunction following Zoster infection are recorded. We present one such case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…17 Another 64 year-old man with HZ reported ED after recovering from his primary presentation with acute urinary retention. 23 A recent case provided by Erol et al presented with urinary retention, ED, and meningitis attributed to sacral HZ. 18 The mechanism by which the occurrence of ED is associated with prior HZ episodes is unclear, yet preliminary evidence has suggested several possibilities.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…17 Another 64 year-old man with HZ reported ED after recovering from his primary presentation with acute urinary retention. 23 A recent case provided by Erol et al presented with urinary retention, ED, and meningitis attributed to sacral HZ. 18 The mechanism by which the occurrence of ED is associated with prior HZ episodes is unclear, yet preliminary evidence has suggested several possibilities.…”
Section: Discussionmentioning
confidence: 96%
“…It is thus plausible that the association detected in this study between ED and HZ may proceed through the serious local inflammation caused by HZ infection at the spinal level. 23 Our study stands out as being able to investigate the association between ED and HZ by using a populationbased epidemiological study which left little room for selection and non-response biases. The strengths of this study also included the availability of a wide-range of sociodemographic data which allowed us to control for confounding and generalize our results to the Taiwanese population as a whole which largely shares a similar sociocultural background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Re-activation within sensory ganglia results in a painful dermatomal zoster rash where as signs of re-activation within the autonomic sacral ganglia includes urinary retention, zoster cystitis, or anorectal dysfunction. [10][11][12] Previous literatures suggested that men are more commonly affected by herpes zoster with bladder involvement than women. 13 Voiding dysfunction is defined as poor coordination between the bladder muscle and urethra.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many reports stating urinary retention secondary to sacral herpes zoster, there are few reports on erectile dysfunction [29,30] and meningitis [31] accompanying sacral herpes zoster. Also, abdominal distension due to the loss of anal reflex has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%